Cannabis users and stigma: A comparison of users from European countries with different cannabis policies - Skliamis, Kostas (European journal of criminology, 2022)
Cannabis is commonly characterized as the most normalized illicit drug. However, it remains a prohibited substance in most parts of the world, including Europe, and users can still be subject to stigmatization. The objective of this study is to assess to what extent and how cannabis users in different countries with different cannabis policies perceive, experience and respond to stigmatization. We conducted a survey in the Dutch coffeeshops among 1225 last year cannabis users from seven European countries, with national cannabis policies ranging from relatively liberal to punitive. Three dimensions of cannabis-related stigma were investigated (discrimination, perceived devaluation and alienation) and a sum score was used to reflect the general level of stigmatization. Perceived devaluation was the highest-scoring dimension of stigma and discrimination the lowest-scoring. The general level of stigmatization was lowest in the Netherlands and highest in Greece. This indicates that punitive cannabis policy is associated with stigma and liberal cannabis policy is associated with de-stigmatization. Besides country, daily cannabis use was also found to be a significant predictor of stigma, but gender, age, household type and employment status were not.